Representation of Women and Nature in Abhi Subedi’s Māyādevikā Sapanā - Mishra, Indira Acharya (Literary Studies, 2021)
The article aims to analyze the depiction of women and nature in Abhi Subedi’s play, Māyādevikā Sapanā [Dreams of Mayadevi] (2008) from the ecofeminist perspective. The play associates women to nature and suggests that there is similarity between the domination of women and exploitation of nature by men in patriarchy. The female characters of the play criticize the patriarchal gender roles based on hierarchy and dualism. They identify patriarchy as the root cause of violence against women and nature. Ecofeminist critics point out that there are conceptual, symbolic, and linguistic connections between feminist and ecological issues. Vandana Shiva and Maria Mies assert that it is the same patriarchal mindset that dominates women exploits the nature. Carolyn Merchant posits that modern capitalism treats nature as a wild female who needs to be tamed and controlled. Val Plumwood argues that western philosophy, which prioritizes reason to emotion, is the key to oppression of women and nature in the modern world. These critics suggest that feminism should also deal with the issues of nature because the destruction of nature harms women more than it harms men. Thus, ecofeminist perspective is relevant to analyze the depiction of women and nature in Māyādevikā Sapanā. The finding of the article reveals that patriarchy is unfriendly to women and nature; and issues of women and ecology are intertwined.